Anti-Inflammatory Effects of Helminth-Derived Products: Potential Applications and Challenges in Diabetes Mellitus Management - Zhu Y; Chen X; Zheng H; Ma Q; Chen K; Li H (Journal of Inflammation Research)
Yunhuan Zhu,1 Xintong Chen,1 Hezheng Zheng,1 Qiman Ma,1 Keda Chen,1 Hongyu Li1,2 1Key Laboratory of Artificial Organs and Computational Medicine in Zhejiang Province, Shulan International Medical College, Zhejiang Shuren University, Hangzhou, Zhejiang, People’s Republic of China; 2Ocean College, Beibu Gulf University, Qinzhou, Guangxi, People’s Republic of ChinaCorrespondence: Hongyu Li, Key Laboratory of Artificial Organs and Computational Medicine in Zhejiang Province, Shulan International Medical College, Zhejiang Shuren University, Hangzhou, Zhejiang, People’s Republic of China, Email hongyu88926@zjsru.edu.cnAbstract: The global rise in diabetes mellitus (DM), particularly type 2 diabetes (T2D), has become a major public health challenge. According to the “hygiene hypothesis”, helminth infections may offer therapeutic benefits for DM. These infections are known to modulate immune responses, reduce inflammation, and improve insulin sensitivity. However, they also carry risks, such as malnutrition, anemia, and intestinal obstruction. Importantly, helminth excretory/secretory products, which include small molecules and proteins, have shown therapeutic potential in treating various inflammatory diseases with minimal side effects. This review explores the anti-inflammatory properties of helminth derivatives and their potential to alleviate chronic inflammation in both type 1 diabetes and T2D, highlighting their promise as future drug candidates. Additionally, it discusses the possible applications of these derivatives in DM management and the challenges involved in translating these findings into clinical practice.Keywords: diabetes mellitus, helminth-derived products, anti-inflammatory, immune modulation